2020
DOI: 10.1039/d0ra04717a
|View full text |Cite
|
Sign up to set email alerts
|

Support effects on catalysis of low temperature methane steam reforming

Abstract: Low temperature (<500 K) methane steam reforming in an electric field was investigated over various catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The author's group investigated SRM in an electric field. [91][92][93][94][95] In this system, constant current is applied after two electrodes are inserted on and under the catalyst bed (Fig. 11(Left)).…”
Section: Othersmentioning
confidence: 99%
“…The author's group investigated SRM in an electric field. [91][92][93][94][95] In this system, constant current is applied after two electrodes are inserted on and under the catalyst bed (Fig. 11(Left)).…”
Section: Othersmentioning
confidence: 99%
“…[39][40][41] This active migration is called surface protonics. It has been revealed that surface protonics plays a key role in activating the cleavage of strong bonds, as in the NRN bond in N 2 , [13][14][15][16][17]42,43 and the C-H bond in hydrocarbons, as in CH 4 [42][43][44][45][46] and methylcyclohexane (MCH). 4,5 Those activations make it possible to catalyze hydrogen production and formation of the hydrogen carrier, even at low temperatures (o500 K).…”
Section: Overviewmentioning
confidence: 99%
“…20,21 Under these circumstances, our group has proposed a catalytic reaction in an electric eld (EF) in which direct current is applied by inserting electrodes at the top and bottom edges of the catalyst layer to promote the reaction. [22][23][24][25] We earlier reported various effects of enhanced activity and lowered apparent activation energy at low temperatures in DRM, 26 RWGS, 27 and CO 2 methanation. 28 However, details of the reactivity of CO 2 and its adsorption ability in the EF have not been claried.…”
Section: Introductionmentioning
confidence: 99%